Solutions to improve the competitiveness of telecommunications in Binh Duong province - Huynh, Chí Tâm; Nguyen, Quỳnh Huy (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The study analyzes the current situation of competitiveness of the telecommunications industry in Binh Duong province, analyzes the resources of enterprises to create competitive advantages in business so that enterprises in the telecommunications industry use more effectively use their resources to meet customer needs better, and at the same time have solutions to improve competitiveness in the period when Vietnam’s economy integrates with other countries in the region and the world. Analyze the achievements, shortcomings, limitations, and causes affecting the competitiveness of the telecommunications industry in the province. From there, the article proposes solutions to focus on Binh Duong Telecommunication that will focus on human, material, and resources to improve the competitiveness of enterprises in the business field.